Early Age of the First Myopic Spectacle Prescription, as an Indicator of Early Onset of Myopia, Is a Risk Factor for High Myopia in Adulthood - Wei-Yu Chiang; Yun-Wen Chen; Yu-Peng Liu; Yung-Hsun Liu; Pei-Chang Wu (Journal of Ophthalmology)
Purpose. The present study investigated the risk factors for high myopia in adulthood, with a focus on the age at which children wore their first spectacles. Methods. Adults aged between 20 and 45 years were invited to complete a questionnaire about age, sex, current refractive error, high myopia in parents, early onset of myopia presented by the age of the first myopic spectacle prescription, refractive power of the first spectacles, and life habits at different educational stages. The associations between these factors and high myopia in adulthood were then evaluated and analyzed. Results. In total, 331 participants were enrolled. Their average refractive error was −4.03 diopters, and high myopia was noted in 27.5% of the study participants. Only 3.3% of participants had fathers with high myopia, while 6.0% had mothers with high myopia. The participants received their first myopic spectacle prescription at a mean age of 13.35 years, with a mean refractive error of −1.63 diopters. The significant risk factors for developing high myopia in adult life were earlier age of the first spectacles prescribed (p<0.001), higher refractive power of the first spectacles (p<0.001), mother with high myopia (p=0.015), and after-school class attendance in senior high school (p=0.018). Those who wore their first spectacles at <9 years of age were more predisposed to high myopia than those who did so at ≧13 years, with an odds ratio of 24.9. Conclusion. The present study shows that earlier onset of myopia, which is presented by the age of the first myopic spectacle prescription, higher myopic refraction of the first spectacles, mothers with high myopia, and after-school class attendance in senior high school are risk factors for high myopia in adulthood. It suggests that delaying the onset of myopia in children is important for the prevention of high myopia in later life.